Neonatal Listeriosis: The Importance of Placenta Histological Examination—A Case Report - Teixeira, Amarilis Batista; Lana, Ana Maria Arruda; Lamounier, Joel Alves; Pereira da Silva, Orlando; Eloi-Santos, Silvana Maria (American Journal of Perinatology Reports, 2011)
Neonatal listeriosis is not a rare disease, but it is infrequently diagnosed and reported in the literature. Herein we report a case of listeria lethal sepsis, followed by increased cytokines levels in the cord blood, in which diagnosis was made possible by histological examination of the placenta.
Keywords: Neonatal listeriosis; chorioamnionitis; sepsis; Listeria monocytogenes; cytokine